Modern approaches to transvenous lead extraction - D. G. Podolyak; A. Yu. Kiprensky; S. A. Mironovich (Российский кардиологический журнал, 2020)
Aim. To show the effectiveness and safety of modern transvenous lead extraction (TLE) techniques used in cardiac surgery.Material and methods. The study included 102 patients (men — 66, women — 36; mean age 58,3±1,7 years). Fifteen (14,7%) patients had infectious indications for TLE, 87 (85,3%) patients — non-infectious. Among the infectious indications (14,7%) were: isolated pocket infection of implantable electronic device (IED) — 13 (12,9%); pocket infection with bacteremia — 1 (0,9%); infectious endocarditis without pocket infection — 1 (0,9%). Of the non-infectious indications, 87 patients (85,3%) had: venous occlusion — 4 (3,9%); chronic pain at IED area — 10 (9,8%); device upgrade — 16 (15,7%); non-functioning (dysfunction, fracture) leads — 57 (55,9%).Results. Using simple traction, 75 (50,4%) leads were removed. TLE technique was used in 56 (37,5%) extractions. Of these, telescoping/rotational mechanical dilators were used in 23 (15,4%) and 33 (22,1%) lead extractions, respectively. In 15 (14,7%) patients with infectious indications, 33 (22,1% of total) leads were removed. In 87 (85,3%) patients with noninfectious indications, 98 (65,8% of total) leads were removed. It was not possible to completely remove 18 (12% of total) leads.Conclusion. Currently, modern TLE techniques have shown their high efficiency and safety. It is confirmed by large international studies such as ELECTRa, LExiCon, PLEXES, where success rate reaches 97,7% and mortality does not exceed 0,5%.The successful application of modern techniques enlarged the list of indications and has been widely used in routine cardiac surgery.